Doubly differential diffraction at a time grating in above-threshold ionization: Intracycle and intercycle interferences - Arbo, Diego (2012)
We analyze the doubly differential electron distribution in atomic above-threshold ionization by a linearly-polarized short-laser pulse. We generalize the one-dimensional (1D) simple man’s model (SMM) of Arbó et al. [19], to a three dimensional (3D) description by using the saddle-point approximation (SPA). We prove that the factorization of the photoelectron spectrum in terms of intracycle and intercycle interference patterns can be extended to the doubly differential momentum distribution. Intercycle interference corresponds to the well-known ATI peaks of the photoelectron spectrum arising from the superposition of electron trajectories released at complex times during different optical cycles, whereas intracycle interference comes from the coherent superposition of trajectories released within the same optical cycle. We verify the SPA predictions by comparison with time-dependent distorted wave calculations and the solutions of the full 3D time-dependent Schrödinger equation (TDSE). An analytical expression for the complete interference pattern within the SPA is presented showing excellent agreement with the numerical calculations. We show that the recently proposed semiclassical description based on the SMM in terms of a diffraction process at a time grating remains unchanged when considering the full 3D problem within the SPA.